2021
DOI: 10.1108/ijoa-10-2020-2440
|View full text |Cite
|
Sign up to set email alerts
|

Strategic alliances and development of intellectual capital: a study of technology-based SMEs

Abstract: Purpose From an absorptive capacity perspective, this study aims to analyse the influence of strategic alliances on the development of intellectual capital. Design/methodology/approach A quantitative study was chosen, with data on technology-based small and medium-sized enterprises (SMEs) in Portugal, leading to 257 valid answers. Findings The results obtained from a structural equation model show that learning/knowledge and efficiency as important functions underlying strategic alliances exert a strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 157 publications
(202 reference statements)
0
7
0
Order By: Relevance
“…Research shows positive effects on firm performance from both IC and alliances (Ulrich et al, 2019). Research also shows the positive impact of alliances on IC (Ferreira et al, 2022). However, a gap exists concerning the effect of IC on alliance formation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Research shows positive effects on firm performance from both IC and alliances (Ulrich et al, 2019). Research also shows the positive impact of alliances on IC (Ferreira et al, 2022). However, a gap exists concerning the effect of IC on alliance formation.…”
Section: Discussionmentioning
confidence: 94%
“…These distinct constructs have developed separate research streams but have begun to be examined together. Within this growing area of work, scholars have sought to understand how strategic alliances impact the development of IC (Ferreira et al, 2022). Joia and Malheiros (2009) focused on the Brazilian transformation industry and found that strategic alliances positively impact IC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because strategic alliances have an impact on human capital, the relationships that industries form with other businesses are becoming increasingly vital for their long-term survival and development. On the other hand, Ferreira et al (2021) in their studies showed that strategic alliances provide a solution for small and medium scale enterprises to overcome intellectual capital resource limits, which has substantial implications for business practice. Prabhudesai et al (2022) in their studies found that while both tangible resources such as finances, component parts etc and intangible resources such as knowledge, expertise etc.…”
Section: Literature Reviewmentioning
confidence: 99%